2019
DOI: 10.1007/s11159-019-09808-y
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical practices in non-formal adult literacy classes in Zambia

Abstract: In Zambia, adult literacy education is mainly provided in the form of non-formal literacy classes, with a general emphasis on the economic purpose of alleviating poverty. The aim is to increase the number of skilled citizens who are literate. Exploring (1) the pedagogical practices used in this context and (2) facilitators' choices of certain teaching-learning methods, this article presents a study which was conducted in Katete District in Eastern Zambia. It involved two literacy programmes; one run by the Gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Terlebih lagi di daerah terisolir atau terpencil seperti penelitian yang dilakukan oleh (Fariyani et al, 2021) bagaimana sekolah alternatif hadir di pedalaman Bangka Belitung sebagai solusi dari belum meratanya pendidikan formal. Senada dengan penelitian di atas, penelitian (Sichula & Genis, 2019) tentang tidak hadirnya sekolah formal di pedalaman Zambia, sehingga melalui kesadaran Lembaga Swadaya Masyarakat (LSM) setempat berdirilah kelas membaca dengan tujuan untuk menurunkan angka buta huruf guna keluar dari belenggu kemiskinan. Ini menggambarkan bagaimana sekolah alternatif tidak hanya berkembang di Indonesia tetapi juga turut berkembang di seluruh dunia.…”
Section: Pendahuluanunclassified
“…Terlebih lagi di daerah terisolir atau terpencil seperti penelitian yang dilakukan oleh (Fariyani et al, 2021) bagaimana sekolah alternatif hadir di pedalaman Bangka Belitung sebagai solusi dari belum meratanya pendidikan formal. Senada dengan penelitian di atas, penelitian (Sichula & Genis, 2019) tentang tidak hadirnya sekolah formal di pedalaman Zambia, sehingga melalui kesadaran Lembaga Swadaya Masyarakat (LSM) setempat berdirilah kelas membaca dengan tujuan untuk menurunkan angka buta huruf guna keluar dari belenggu kemiskinan. Ini menggambarkan bagaimana sekolah alternatif tidak hanya berkembang di Indonesia tetapi juga turut berkembang di seluruh dunia.…”
Section: Pendahuluanunclassified
“…In Freire's (1969 seminal work Pedagogy of the Oppressed, the Brazilian activist and educator argued that liberation for marginalized groups can occur through communal education. A framework of "critical pedagogy encourage [s] students to identify inequalities in society and redefine their role in changing society" (Yep, 2014, p. 51) and allows students to think critically about the Englishes (both spoken or written) that they interact with, raising the learner's awareness of their environment and allowing for liberation from oppressive political and cultural ideologies (Sichula, 2018). By bringing a critical pedagogy into a communal classroom, students can engage in a critical examination of societal injustices that immigrants or non-standard English speakers experience.…”
Section: Curriculum Frameworkmentioning
confidence: 99%
“…English has a long and troubled history as a form of colonization. The forced acquisition of the English language and Western-style education has uprooted and destroyed various diverse languages and cultures (Coelho & Henze, 2014;Sichula, 2018). "Named languages" (such as English, Kazakh, Spanish, or Basque) are social constructs arranged and maintained through political or social entities.…”
Section: Translanguagingmentioning
confidence: 99%
“…Recent research into adult literacy facilitators (ALFs) (e.g. Rogers et al 2003Rogers et al [1989; Paluch 2013;Warkineh et al 2018;Gizaw et al 2019;Maleki et al 2019;Sichula and Genis 2019) has shown that most of those who teach literacy to adults in developing countries are part-timers from the locality. There are of course others, such as primary school teachers who are asked to teach adults outside of school lesson times, and there are in some countries a relatively small number of trained, qualified, professional adult educators under various titles, but most ALFs around the world are unqualified occasional employees, working part-time, on shortterm contracts.…”
Section: Introductionmentioning
confidence: 99%